In vitro digestibility and prebiotic activities of a sulfated polysaccharide from Gracilaria Lemaneiformis. (January 2020) - Han, Rui; Pang, Daorui; Wen, Lingrong; You, Lijun; Huang, Riming; Kulikouskaya, Viktoryia
Graphical abstract: Highlights: SP was scarely degraded during digestion but mostly degraded in fermentation. SP (53.7%) was utilized by microbes to produce 50.07 mM SCFAs at 48 h. SP could modulate the composition of gut microbes in a mild way. Proteobacteria and Firmicutes were the most sensitive phyla in fermentation. Abstract: The study explored the changes of a sulfated polysaccharide (SP) from Gracilaria Lemaneiformis during simulated human digestive system. The results showed SP was scarcely degraded without significant difference. Moreover, the results of fermentation in vitro indicated 53.7% of SP were utilized by gut microbiota with the molecular weight decreasing by 59.41% at 48 h. Meanwhile, 50.07 ± 2.82 mM of short chain fatty acids were produced in culture medium. Besides, in contrast with the regulation of galacto-oligosaccharide sacrificing diversity and richness of community, SP could regulate the composition of microbiota in a mild way. What's more, Proteobacteria and Firmicutes were the most sensitive phyla responding to changes of pH values in this study. And Sutterella, Phascolarctobacterium, Parabacteroides, Lachnospiraceae_UCG-004, Desulfovibrio and Bacteroides were dominant genera for degrading and utilizing SP. Furthermore, the metagenomic function characteristics of microbes might be changed by SP. Thus, SP could be a potential prebiotic.